2018
DOI: 10.1007/s12035-018-1314-3
|View full text |Cite
|
Sign up to set email alerts
|

Memory Decline and Its Reversal in Aging and Neurodegeneration Involve miR-183/96/182 Biogenesis

Abstract: Aging is characterized by progressive memory decline that can lead to dementia when associated with neurodegeneration. Here, we show in mice that aging-related memory decline involves defective biogenesis of microRNAs (miRNAs), in particular miR-183/96/182 cluster, resulting from increased protein phosphatase 1 (PP1) and altered receptor SMAD (R-SMAD) signaling. Correction of the defect by miR-183/96/182 overexpression in hippocampus or by environmental enrichment that normalizes PP1 activity restores memory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…Intriguingly, previous studies have demonstrated the suppression of miR-182 cluster by protein phosphatase 1 (PP1) as a removable constraint on memory formation (Genoux et al, 2002;. The authors describe the reduced expression of miR-182 and the associated cognitive decline as reversible by overexpression of the miR-182 cluster (Jawaid et al, 2019), which is underexpressed during aberrant PP1 activity in aging and neurodegeneration. It is therefore possible that QR2 is placed further downstream as part of the effect of PP1-mediated miR-182 regulation following novel taste stimulus in the aIC (Adaikkan and Rosenblum, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, previous studies have demonstrated the suppression of miR-182 cluster by protein phosphatase 1 (PP1) as a removable constraint on memory formation (Genoux et al, 2002;. The authors describe the reduced expression of miR-182 and the associated cognitive decline as reversible by overexpression of the miR-182 cluster (Jawaid et al, 2019), which is underexpressed during aberrant PP1 activity in aging and neurodegeneration. It is therefore possible that QR2 is placed further downstream as part of the effect of PP1-mediated miR-182 regulation following novel taste stimulus in the aIC (Adaikkan and Rosenblum, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…For example, miR-96-5p expression has been associated with the coordination of neural crest [49] and auditory hindbrain development [50], as well as the induction and progression of neuronal differentiation [51][52][53]. It has also been shown to be involved in the regulation of long-term memory [54,55] and pain sensitivity [56]. Furthermore, mutations in the miR-96-5p seed region have been linked to progressive hearing loss due to defects in the cochlear hair cells [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both Tau and TDP-43 can be phosphorylated by Tau tubulin kinases 1 and 2 (TTBK1/2) (97,133), and elevated levels of TTBK1/2 have been identified in brains of AD (134) as well as FTD-Tau and FTD-TDP patients (98), where they co-localize with pTDP-43 (97). A phosphatase that was found to be elevated in the aging brain and cortices of ALS patients is the nuclear PP1 isoform PP1␥ (158), furthermore indicating that misregulated phosphorylation and dephosphorylation events may contribute to pathological protein aggregation and neurodegeneration.…”
Section: Arginine Methylation and Phosphorylation As Regulators Of Llmentioning
confidence: 99%